Analisis Resiko Operasional UMKM Pecel Lele dan Ayam Lamongan Kang Adi William Iskandar Medan Tembung - Ricky Louis Naibaho; Liston Rivaldo Sitorus; Jan Moris Saragih; Putri Kemala Dewi Lubis; Rossy Pratiwi Sihombing (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
Many MSMEs, especially catfish and chicken pecel businesses, still pay little attention to the risks that affect their business. This research aims to analyze and identify operational risks in Kang Adi's Pecel Lele and Lamongan Chicken MSMEs. This research uses a qualitative descriptive method by collecting data through interviews and documentation. The research results show that there are several operational risk factors with impacts varying from low, medium to large. Apart from that, the frequency with which risks occur also varies, from very often to rarely. To anticipate these risks, business owners must be more concerned and proactive in identifying risks in order to minimize losses. Actions that need to be taken to anticipate and avoid operational risks at Kang Adi's Pecel Lele and Ayam Lamongan MSMEs include developing a comprehensive risk management system, employee training, and regular reviews of operational procedures. In this way, this business can be better prepared to face various challenges and risks that may arise in the future.